Respuesta :

Answer:

Simplifying

(5n + -3) + -1(-2n + 7) = 0

Reorder the terms:

(-3 + 5n) + -1(-2n + 7) = 0

Remove parenthesis around (-3 + 5n)

-3 + 5n + -1(-2n + 7) = 0

Reorder the terms:

-3 + 5n + -1(7 + -2n) = 0

-3 + 5n + (7 * -1 + -2n * -1) = 0

-3 + 5n + (-7 + 2n) = 0

Reorder the terms:

-3 + -7 + 5n + 2n = 0

Combine like terms: -3 + -7 = -10

-10 + 5n + 2n = 0

Combine like terms: 5n + 2n = 7n

-10 + 7n = 0

Solving

-10 + 7n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10' to each side of the equation.

-10 + 10 + 7n = 0 + 10

Combine like terms: -10 + 10 = 0

0 + 7n = 0 + 10

7n = 0 + 10

Combine like terms: 0 + 10 = 10

7n = 10

Divide each side by '7'.

n = 1.428571429

Simplifying

n = 1.428571429

Answer:

79-10

Step-by-step explanation:

Brainliest please.